Keratopathy in Patients with Adenoviral Keratoconjunctivitis: Evaluation of the Effectiveness of Modern Interferon Preparations - E. A. Drozdova; S. Yu. Golubev; V. V. Brzheskiy; E. A. Romanova; V. A. Kireeva; E. V. Berdnikova (Oftalʹmologiâ, 2023)
It is considered, that one of the main directions of treatment of adenovirus conjunctivitis is the appointment of interferon alpha-2b in combination with diphenhydramine, which until recently was provided by the only original drug. In 2020, the first generic drug, Interferon-Oftalmo, would be registered in Russia.The purpose: to evaluate and compare the efficacy, safety and tolerability of treatment of patients with keratopathy against the background of adenovirus keratoconjunctivitis with Interferon-Oftalmo and Oftalmoferon.Material and methods. The comparative analysis included completed cases of treatment of 51 patients (102 eyes) aged 18–75 years with clinical signs of keratopathy against the background of epidemic adenoviral keratoconjunctivitis. Patients of the first group (n = 27, 54 eyes) on the background of tear replacement therapy received eight instillations of the drug Interferon-Ophthalmo, the second (n = 24, 48 eyes) received Oftalmoferon. The observation period was 15 days. Treatment efficacy was assessed based on a quantitative analysis of the dynamics of clinical symptoms of inflammation and the state of the cornea, the severity of subjective manifestations of ocular surface xerosis using the ocular surface damage index (OSDI), as well as the stability of the tear film. Safety and tolerability were also evaluated.Results. Against the background of complex therapy, which included the instillation of Interferon-Ophthalmo or Oftalmoferon, all patients showed comparable dynamics in the relief of the inflammatory process and keratopathy. This was expressed in a statistically significant decrease in the severity of foreign body sensation, lacrimation, itching, eyelid edema, conjunctival edema and hyperemia, follicular reaction, conjunctival hemorrhages, punctate keratopathy, subepithelial infiltrates in the cornea. In both groups, there was a steady downward trend in OSDI against the background of an increase in the stability of the tear film and an increase in maximally corrected visual acuity. The safety and tolerability profile of the drugs was assessed as comparably favorable.Conclusion. The inclusion of the drug Interferon-Oftalmo in the complex therapy of adenoviral epidemic keratoconjunctivitis allows us to expect a comparable effect on the course of the disease compared to the original drug Oftalmoferon.